PEER TO PEER LENDING ANALYSIS OF SHARIA MAQASHID PERSPECTIVE - Abdulloh Munir (Qawanin: Jurnal of Economic Syaria Law, 2023)
The implementation of fintech peer to peer lending (P2P lending) has benefits that are in accordance with maqashid sharia and problems to date, so it is necessary to explore the extent to which lenders are implementing it to determine the eligibility of borrowers. However, it is growing and becoming the concern of the government to create benefits and common goals. The research method is in the form of literature research with data reduction analysis techniques, displays and drawing conclusions. The results prove that P2P lending analysis uses 4P (personality, purpose, prospect, payment), 5C (character, capacity, capital, collateral, condition of economy), credit scoring, regional and demographic surveys and others. Referring to maslahat in the form of economic fulfillment and domination of benefit rather than harm in P2P lending, while maqashid sharia in the form of: protecting religion can be seen from the fulfillment of P2P lending contracts and agreements; take care of the soul because it is used for the survival of the community; keep common sense because the P2P lending practice process must go through careful consideration, complete information and knowledge; taking care of offspring because it is used to fulfill family survival; and guarding property because it demands the best possible financial management. This benefit must be prioritized because technology cannot be separated from economic activity, urgent needs of the community and a solution to difficult access for borrowers or MSMEs.